Pollution Characteristic and Source Analysis of Heavy Metals in Atmospheric PM2.5 During Heating Season in Taiyuan and Surrounding Area - Zhilei WANG; Xiaofeng LIU; Shuting ZHANG; Huiling BAI; Ling MU; Xuan LI (Taiyuan Ligong Daxue xuebao, 2021)
In order to study the pollution characteristics and sources of heavy metals in PM2.5 around Taiyuan City during the heating season, atmospheric PM2.5 samples were collected in Taiyuan City and Yuci University Town in January 2018. Plasma mass spectrometry was used to determine 10 heavy metal elements. Enrichment factor method and cluster analysis method were used to clarify their sources. The backward trajectory method was adopted to analyze the influence of air mass migration. The results show that zinc, lead, and manganese were the three elements with the highest heavy metal concentrations in the heating season PM2.5 in Taiyuan City and Yuci University Town, accounting for 77.80% and 89.06% of the total concentration of the 10 elements, respectively. The enrichment level of Cu, Zn, As, Cd, and Pb in Taiyuan City and Yuci University Town PM2.5 was above moderate. The main source of heavy metals in PM2.5 in the heating season of Taiyuan City and Yuci University Town was coal-fired sources. Taiyuan City and Yuci University Town were affected by the long-distance air flow from the northwest. The dust formed by the flow was one of the natural sources of 10 heavy metals in PM2.5 in Taiyuan City and Yuci University Town. In the heating season of the same year, December was the month with the highest heavy metal concentration in PM2.5.